Delivery of care, seizure control and medication adherence in women with epilepsy during pregnancy. (August 2022) - Askarieh, Amber; MacBride-Stewart, Séan; Kirby, Jack; Fyfe, David; Hassett, Richard; Todd, Jonathan; Marshall, Alex D; Leach, John Paul; Heath, Craig A
Highlights: Less than 50% of women with epilepsy (WWE) were reviewed by services pre-conception Only two thirds were reviewed during pregnancy, majority in second/third trimester Almost 60% of WWE had poor adherence to their anti-seizure medication (ASM) Routine health data can identify pregnant WWE, enabling timely access to services Accessing prescribing data can improve ASM adherence in WWE during pregnancy Abstract: Purpose: To evaluate service access for women with epilepsy (WWE) during pregnancy; to determine seizure frequency and rates of adherence to anti-seizure medication (ASM). Methods: Between June 2019-June 2020, pregnant WWE within NHS Greater Glasgow and Clyde health-board were identified from the National Obstetric Register. A manual review of electronic patient records was undertaken to ensure diagnostic accuracy, as well as determine contact with epilepsy services and documented seizures. Medication dispensing records were obtained six months before and six months after midwifery booking and measures of ASM adherence calculated. Results: Between June 2019-June 2020, 4592 women were registered with a pregnancy. Eighty-five (1.9%) were identified as having active epilepsy (generalised- 40/85 (47.0%), focal- 35/85 (41.2%), unclassified- 10/85 (11.8%)). Preconceptually, 42/85 WWE (49.4%) had input from epilepsy services. Only 59/85 (69.4%) were reviewed during pregnancy (First trimester- 21/59 (35.6%), Second trimester- 25/59 (42.4%) and Third trimester- 13/59 (22.0%)). Seizure occurrence was documented in 37/85 WWE (43.5%) during the antenatal/postnatal period. 71/85 WWE (83.5%) were prescribed ASM. Poor adherence was noted in 50/85 (58.9%) and a documented seizure recorded in 26/50 (52.0%) of these women. Conclusion: Too many WWE do not receive input from epilepsy services during pregnancy, leaving some with poor ASM adherence and continued seizures. We aim to use "near-live" obstetric and dispensing data to facilitate early identification of WWE, promoting timely access to epilepsy specialists. This will also provide an opportunity to address concerns regarding ASM safety and allow medication dose changes to be considered.